Iron and vitamin B12 deficiency anaemia in a vegetarian: a diagnostic approach by enzyme-linked immunosorbent assay and radioimmunoassay - Iamaroon A. (2014)
This article presents the case of a 46-year-old vegetarian who had a painful dry socket in the left third molar areas. Since the patient's general appraisal was anaemic, investigations for haematological status, folic acid and vitamin B12 were performed. The results revealed that the patient was severely iron deficient and slightly vitamin B12 deficient.